Exploring factors associated with HIV secondary stigma among adolescents and young adults in Uganda: A cross-sectional study. Issue 4 (3rd April 2022) - Small, Eusebius; Nikolova, Silviya Pavlova; Zhou, Yuan; Okumu, Moses
ABSTRACT: HIV stigma is a public health problem. It refers to irrational judgments and attitudes towards people living with or at risk of HIV. Among adolescents and young adults living with HIV, stigma can negatively influence help-seeking decisions and impede HIV prevention efforts. The present study aimed to explore social-ecological factors associated with HIV-related stigma using a cross-sectional study design. Data used were from the 2016 Uganda Demographic and Health Survey [UDHS] of young men ( n = 2214) and young women ( n = 8058) aged 15–24 years. We conducted a gender disaggregated multivariable logistic regression to understand social-ecological factors associated with HIV secondary stigma. An overwhelming majority of participants (85%) indicated that secondary HIV stigma was associated with factors such as gender, ethnicity, education, wealth, cultural attitudes, and testing experiences. The study concludes that many young people living with HIV experience stigma in Uganda. Therefore, the government of Uganda, health professionals, and researchers should consider developing interventions that address HIV stigma and discrimination. Supportive programmes, such as peer support services and community-based interventions, are needed to help young people living with HIV learn to cope with the illness.